KAJIAN KEARIFAN LOKAL USAHATANI PADI SAWAH PADA MASYARAKAT ETNIS BALI DI DESA WERDHI AGUNG TIMUR KECAMATAN DUMOGA TENGAH - Yanubi, Cheren; Taroreh, Melissa Lady Gisela; Tambas, Jane Sulinda (Sam Ratulangi University, 2022)
This study aims to examine and describe local wisdom in lowland paddy farming in Balinese ethnic communities in Werdhi Agung Timur Village, Dumoga Tengah District. This research was conducted for 3 months starting from June to August 2021. The data used in this study were primary data and secondary data. Primary data were obtained through direct interviews with 1 resource person as the Secretary of Werdhi Agung Timur Village and 7 informants as the Subak Banyu Harapan group and also padddy farmers using questionnaires. Secondary data was obtained from the government office of Werdhi Agung Timur Village. The sampling method was carried out using the snowball sampling method. The data analysis method used is descriptive qualitative. The results showed that there were 15 forms of local wisdom in lowland rice farming in the people of Werdhi Agung Timur Village, Dumoga Tengah District.